A Dozen Reasons for Including Conceptual Physical Education in Quality Secondary School Programs. Issue 3 (23rd March 2020) - Corbin, Charles B.; Kulinna, Pamela Hodges; Sibley, Benjamin A.
Abstract : As outlined in this article, conceptual physical education (CPE) uses a text and classroom sessions to teach healthy lifestyle concepts and principles as well as self-management skills that promote lifelong fitness and active living. CPE programs are meant to be an important part of quality physical education (PE) programs. A dozen reasons are provided to help physical educators gain the support of all stakeholders including students, parents, administrators, board members, and members of the community.